2016
DOI: 10.1007/s00894-016-2976-2
|View full text |Cite
|
Sign up to set email alerts
|

Does the position of the electron-donating nitrogen atom in the ring system influence the efficiency of a dye-sensitized solar cell? A computational study

Abstract: We have reported a number of new metal-free organic dyes (2-6) that have cyclic asymmetric benzotripyrrole derivatives as donor groups with peripheral nitrogen atoms in the ring, fluorine and thiophene groups as π-spacers, and a cyanoacrylic acid acceptor group. Density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations were employed to examine the influence of the position of the donor nitrogen atom and π-conjugation on solar cell performance. The calculated electron-injection driving force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 97 publications
0
20
0
Order By: Relevance
“…It can also be seen from Figure 1 that all the different dyes considered in this work have their LUMO energies above the CB edge of TiO 2 (see Figure 1), thus allowing a favorable interfacial electron injection from the excited dyes to the CB of TiO 2 . Furthermore, we found that for all the considered dyes, the HOMO lies below the iodide redox potential (−4.58 eV) 32,78 (see Figure 1). All EW substituents lower both E HOMO and E LUMO , in fact more significantly for the donor substituents, whereas the opposite is true for the ED substituents.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It can also be seen from Figure 1 that all the different dyes considered in this work have their LUMO energies above the CB edge of TiO 2 (see Figure 1), thus allowing a favorable interfacial electron injection from the excited dyes to the CB of TiO 2 . Furthermore, we found that for all the considered dyes, the HOMO lies below the iodide redox potential (−4.58 eV) 32,78 (see Figure 1). All EW substituents lower both E HOMO and E LUMO , in fact more significantly for the donor substituents, whereas the opposite is true for the ED substituents.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…However, the regeneration of the dye reflected by the redox mediator Δ G regen also influences J SC . Higher negative values of the Δ G regen will have an adverse effect on the J SC with respect to the efficiency of the dye . Δ G regen values higher (more toward zero) than −0.36 eV ( D5 , Table ) cause a higher J SC than the one for the D5 dye.…”
Section: Results and Discussionmentioning
confidence: 98%
“…7 However, metal base dyes have demerits like leaching from the semiconductor surface and heavy metal environmental hazards as well as higher cost and limited resources. 39 Organic dyes are alternatives to overcome such problems.…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that for efficient electron injection into anode the HOMO should be localized over the D-S part and the lowest unoccupied molecular orbital (LUMO) of the dye should be localized near the anchoring group and above the conduction band edge of the semiconductor electrode (here TiO 2 ). 39 The HOMO-LUMO pictures of spacer group 1-6 and 6-D are given in Fig. 6 suggests that for all the systems HOMO orbitals are localized over D-S-A part whereas the LUMO orbitals are localized over the S-A part.…”
mentioning
confidence: 95%
“…The experimentally reported maximum absorption spectra (λ max ) are compared with the λ max obtained at different DFT functionals. The reported dyes ( 1 , 3 , 5 , 7 , and 9 ) were optimized with B3LYP/6–31G* level of theory and the λ max values were calculated using different DFT functionals with larger basis set: B3LYP/6‐31 + G*, M062X/6‐31 + G*, ωB97XD/6‐31 + G*, bp86/6‐31 + G*, PBE0/6‐31 + G* MPW1K/6‐31 + G*, and CAM‐B3LYP/6‐31 + G* (Table ) . The calculated results suggest that the ωB97XD/6 − 31 + G* method is in better agreement with the experiment λ max than other functionals and hence it is used for further studies.…”
Section: Resultsmentioning
confidence: 99%